Leadership, Distributive Justice and Quality of Work Life on Employee Performance - Andi Renovandy; Ria Mardiana (Scientia Integritas Utama, 2022)
The development and improvement of the quality of the company's human resource management will have implications for improving the performance and performance of employees. Human resource management influences employee performance through creating value or using human resource expertise related to broadly targeted management practices. What is the relationship between leadership, distributive justice, great of work lifestyles on employee performance? There are nevertheless few researchers who discover this query. This study ambitions to have a look at the effect of (i) leadership has a enormous impact on employee overall performance; (ii) distributive justice has a large impact on worker overall performance; (iii) great of labor life has a great impact on employee performance. This research was conducted at the Port of Indonesia (Persero) Container Terminal, Makassar Branch. The type of data to be used in this study is in the form of qualitative data and quantitative data. Sources of data used in this research are primary data and secondary data. The population in this study were all employees of the Indonesian Port Container Terminal (Persero) Makassar Branch. The population of this study consisted of 71 permanent (organic) employees, while 329 outsourced employees. Determination of the number of samples as many as 148 respondents. This study uses a survey method in data collection. The analysis technique used is validity test, reliability test, descriptive analysis, and multiple linear regression analysis and different test. The results of the study show that the variables of leadership, distributive justice, and quality of work life have a positive and significant effect on employee performance.